(untitled) (Práxis Educativa, 2025)
Resenha: ALMEIDA, Dóris Bittencourt; CUNHA, Maria Teresa Santos (org.). Arquivos pessoais, patrimônio e educação: ego-documentos em cena. Curitiba: Appris, 2024. 222 p.